IMPACT DE LA PANDEMIE DE LA MALADIE A CORONAVIRUS 2019 SUR LE TRANSPORT AERIEN DES MARCHANDISES EN DESTINATION DE KISANGANI DE 2019 A 2020 Cas de la compagnie Congo Arways - Sosthène, KAYUMBA SADIKI (IJRDO - Journal of Business Management, 2022)
In conducted this study on the impact of the 2019 Coronavirus disease pandemic, the main objective was to verify if during the period selected for this study (2019 to 2020), the air transport of goods in destination of Kisangani by Congo Airways was not negatively affected. Thus, to achieve this, the documentary technique allowed us to collect the data, which we processed statistically, using the method of ordinary least squares. From the results of this processing, we have noted that during the period retained for this research, Congo Airways has transported goods to Kisangani, with an estimated drop of 28.5 kilograms per month, consequently confirming the main hypothesis of the present research.